Pengembangan Buku Saku Digital Pelatihan Hygiene Sanitasi Pada Penjamah Makanan Kampung Kue Rungkut Surabaya - Januar Trihardi; Sri Handajani; Mauren Gita; Romadhoni Romadhoni (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2023)
This study aims to determine: (1) The results of the development of a digital pocketbook of sanitation hygiene training for food handlers of Rungkut Surabaya cake village, (2) The feasibility of digital pocketbook material, (3) The feasibility of digital pocketbook media, (4) The response of food handlers of Rungkut Surabaya cake village to the feasibility of digital pocketbook of sanitation hygiene training. This research method is R&D with the PLOMP development model with only four stages due to the limited time and costs required for research. Validation of digital pocketbooks involves three material experts and three media experts, The object of research is a digital pocketbook. Questionnaires used in data collection are material validation sheets, media and digital pocketbook user response questionnaires. The data analysis technique was carried out descriptively quantitative. The results showed: (1) The results of the digital pocket book that have been made in the form of online links covering hygiene sanitation material, (2) The digital pocket book material is feasible with an average value of 85% including the interpretation of very feasible and (3) The digital pocket book media is feasible with an average value of 87% including the interpretation of very feasible (4) The response of food handlers obtained an average score of 86% with a very good interpretation. This implies that the digital pocket book of the research results can be used in training and learning.